The Rise of the BRICS in Africa the geopolitics of south-south relations - Carmody, Padraig (New York Zed Books, 2013)
A little over a decade ago Africa was being spoken of in the media as the 'lost' or 'hopeless' continent. Now it has some of the fastest growing economies in the World, largely because of the impact of the BRICS: Brazil, India, Russia, China and South Africa.
Includes Bibliographies and index
Keywords: Development